Aplikasi Pengingat Lokasi dan Pembayaran Parkir - Muhammad Rifqi; Andri Andri (Jurnal Ilmiah FIFO, 2019)
Nowadays people especially those in the metropolitan area or developing their livelihood on a smart phone. Based on this, there arose an idea to expand and enrich the smart phone functions not only as a medium of communication, but one of them as a device that can help people in carrying out daily activities. One of them as a device that can help people to supplement the existing weaknesses in him, such forgetfulness. Forgetting the parking location is one of human weakness because of forgetfulness. That requires a device that can help people to remember the location of parking their vehicles. In addition, the smart phone also can help people to make payment transactions more practical. Then, if a parking location reminder device combined with payment at the parking booth will be a very useful tool and efficient. With smart phone technology is increasingly sophisticated and technology support NFC (Near Field Communication) device is expected to be a solution to deal with problems that often occur in parking location and minimize queuing at the ticket counter payment of parking